2017
DOI: 10.1080/2162402x.2017.1356145
|View full text |Cite
|
Sign up to set email alerts
|

EGFR mutation correlates with uninflamed phenotype and weak immunogenicity, causing impaired response to PD-1 blockade in non-small cell lung cancer

Abstract: Patients with mutations showed unfavorable response to programmed cell death-1 (PD-1) blockade immunotherapy in non-small cell lung cancer (NSCLC). Yet the underlying association between mutation and immune resistance remains largely unclear. We performed an integrated analysis of PD-ligand 1(PD-L1)/CD8 expression and mutation profile based on the repository database and resected early-stage NSCLC in Guangdong Lung Cancer Institute (GLCI). Meanwhile, 2 pool-analyses were set to clarify the correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
325
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(348 citation statements)
references
References 37 publications
17
325
4
2
Order By: Relevance
“…Imperfectly generated antitumor immunity may be associated with certain tumor characteristics of particular molecular and histological traits. These characteristics include tumors with EGFR mutation, which exhibit weaker immunogenicity, less abundant immune cell infiltration in the tumor microenvironment and lower responsiveness to ICI monotherapy . This finding echoes recent results from the IMpower 130 trial in which the population with EGFR and ALK driver mutations did not receive a boost in treatment efficacy from the addition of ICIs; the IMpower 150 trial showed that only the administration of bevacizumab significantly improved the treatment efficacy of ICIs in such patients .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Imperfectly generated antitumor immunity may be associated with certain tumor characteristics of particular molecular and histological traits. These characteristics include tumors with EGFR mutation, which exhibit weaker immunogenicity, less abundant immune cell infiltration in the tumor microenvironment and lower responsiveness to ICI monotherapy . This finding echoes recent results from the IMpower 130 trial in which the population with EGFR and ALK driver mutations did not receive a boost in treatment efficacy from the addition of ICIs; the IMpower 150 trial showed that only the administration of bevacizumab significantly improved the treatment efficacy of ICIs in such patients .…”
Section: Discussionsupporting
confidence: 57%
“…These characteristics include tumors with EGFR mutation, which exhibit weaker immunogenicity, less abundant immune cell infiltration in the tumor microenvironment 27 and lower responsiveness to ICI monotherapy. 28 This finding echoes recent results from the IMpower 130 trial in which the population with EGFR and ALK driver mutations did not receive a boost in treatment efficacy from the addition of ICIs; 24 the IMpower 150 trial showed that only the administration of bevacizumab significantly improved the treatment efficacy of ICIs in such patients. 21 Consistent with these findings, our results also showed that patients in the EGFR mutation subgroup who received single agent ICI treatment exhibited the shortest PFS (Fig 4b).…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies of immune checkpoint inhibitors showed that tumors with EGFR sensitizing mutations had significantly lower response rates compared to wild-type EGFR tumors, 23 as a result of less abundant immune cell infiltration and weaker immunogenicity in the EGFR-mutant tumor microenvironment. 24 The lower infiltration of immune cells, including CD8 T and CD4 T regulatory and myeloid-derived suppressor cells, indicates a reduction in the number of target cells that VEGF can engage to augment immunosuppression through the VEGF/VEFG-R2 signaling pathway, 6,7,25 thereby diminishing the role VEGF plays in this microenvironment context and leading to moderation of the beneficial effect of bevacizumab. In line with this, treatments using VEGF and VEGFR blocking agents in combination with checkpoint protein inhibitors, mainly for non-driving mutation NSCLCs, are being actively investigated with encouraging results.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Increasing evidence suggests that noninflamed tumors characterized by poor infiltration of lymphocytes, rare PD-L1 expression, and increased immunosuppressive components in the tumor microenvironment (TME) contribute to the lower-thanexpected efficacy of PD-1/PD-L1 inhibitors. 20,21 Previous studies have demonstrated that inhibition of EGFR by EGFR-TKIs modulates the TME through several mechanisms, including attenuation of the suppressive function of Tregs and enhancement of the antitumor activity of cytotoxic T cells. 22,23 Nevertheless, present evidence is still not sufficient to explain the unsatisfactory results of PD-1/PD-L1 inhibitors when used either as monotherapy or in combination with EGFR-TKIs in EGFR-mutant NSCLCs.…”
Section: Introductionmentioning
confidence: 99%